2014
DOI: 10.1111/bju.12405
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum albumin is associated with mortality and complications after radical cystectomy

Abstract: Objective To determine the association between preoperative serum albumin and mortality and postoperative complications after radical cystectomy and urinary diversion. Patients and Methods We conducted a retrospective review of 1097 radical cystectomies performed for the treatment of bladder cancer between 1992 and 2005. All data were entered prospectively into a hospital-based complications database. We used multivariable logistic regression to assess the association between preoperative serum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 14 publications
6
51
0
1
Order By: Relevance
“…Garg et al also demonstrated that hypoalbuminemia significantly increased the risk of complications within 90 days of RC. 12 Specifically, neurologic and wound complications occurred more frequently in patients with decreased pre-operative serum albumin, while other major complications, including cardiac, gastrointestinal, genitourinary, infectious, bleeding, pulmonary, and thromboembolic were not significantly associated. Despite a larger cohort (N=1097), this series included only patients from a single tertiary specialty oncology hospital.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Garg et al also demonstrated that hypoalbuminemia significantly increased the risk of complications within 90 days of RC. 12 Specifically, neurologic and wound complications occurred more frequently in patients with decreased pre-operative serum albumin, while other major complications, including cardiac, gastrointestinal, genitourinary, infectious, bleeding, pulmonary, and thromboembolic were not significantly associated. Despite a larger cohort (N=1097), this series included only patients from a single tertiary specialty oncology hospital.…”
Section: Discussionmentioning
confidence: 85%
“…11,12 Lambert et al reported that patients with a serum albumin < 3.5 g/dL had a 22% greater overall complication rate compared to patients with a normal albumin (>3.5 g/dL), even when controlling for multiple covariates. 11 However, their sample size was small (n = 187), and the study was not specifically designed to evaluate complications, which were therefore neither systematically nor prospectively ascertained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous short-term mortality studies in RC patients are numerous and identify rates from 2.4 to 8.4% [7][8][9]. Unfortunately these rates are oftentimes assessed at different time-points after PC (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential disadvantage of RC consists of its non-negligible perioperative mortality, which may range from 2.4 to 7.9% at centers [7,8] of excellence and from 5.4 to 8.4% in the community [9][10][11]. Perioperative mortality appears lower for PC, evidenced by 1.8% in-hospital mortality after this procedure [12].…”
Section: Introductionmentioning
confidence: 99%